Indigenous Toponyms as Pedagogical Tools: Reflections from Research with Tl’azt’en Nation, British Columbia - Heikkilä, Karen; Fondahl, Gail (Geographical Society of Finland, 2010)
Apart from conventional understandings of its utilitarian function as spatial labels (often eponymous in character), toponymy is seldom appreciated as palimpsest or for the layers of meaning it assumes, conveyed in place-name etymologies and local knowledge associated with the named places. Over the years, a growing body of literature has emerged on the use of toponymy in several research fields: the range spans from linguistic investigations into place-names and naming practices to the use of place-names in tracking environmental change, locating places of archaeological interest and understanding the knowledge possessed by local communities about the natural environment. The latter focus describes place-names research with Tl’azt’en Nation, the Dakelh-speaking people whose territory lies in the Stuart-Trembleur watershed of central British Columbia, Canada. From the perspective that indigenous place-names communicate knowledge about the natural world, indigenous language and(oral) history, this paper will draw upon examples of Dakelh place-names to put forth the argument that toponymy should be considered in curriculum not only as a means to educate about local geography and history, but to instill awareness and appreciation of, as in the case of indigenous place-names, other epistemologies or non-western ways of understanding the world.